Biological soft X‐ray tomography on beamline 2.1 at the Advanced Light Source. (30th September 2014) - Le Gros, Mark A.; McDermott, Gerry; Cinquin, Bertrand P.; Smith, Elizabeth A.; Do, Myan; Chao, Weilun L.; Naulleau, Patrick P.; Larabell, Carolyn A.
<x xml:space="preserve">Abstract</x> Beamline 2.1 (XM‐2) is a transmission soft X‐ray microscope in sector 2 of the Advanced Light Source at Lawrence Berkeley National Laboratory. XM‐2 was designed, built and is now operated by the National Center for X‐ray Tomography as a National Institutes of Health Biomedical Technology Research Resource. XM‐2 is equipped with a cryogenic rotation stage to enable tomographic data collection from cryo‐preserved cells, including large mammalian cells. During data collection the specimen is illuminated with `water window' X‐rays (284–543 eV). Illuminating photons are attenuated an order of magnitude more strongly by biomolecules than by water. Consequently, differences in molecular composition generate quantitative contrast in images of the specimen. Soft X‐ray tomography is an information‐rich three‐dimensional imaging method that can be applied either as a standalone technique or as a component modality in correlative imaging studies.